Analysis of Infiltration Wells Needs in Flood Management in Sunyaragi Urban Village Cirebon City - Muhamad Nur Afandi; Ola Maula Hasbiya Fauzi; Dhea Oktaviani; Awliya Tribhuwana (Riviera Publishing, 2025)
The development of a city results in increased urbanization. This development leads to changes in land use in urban areas, creating large areas covered by buildings and roads, which reduces infiltration and increases surface runoff. With high rainfall of 147.238 mm per month, Sunyaragi Village often experiences flooding during the rainy season, especially on St. Taman Pemuda. This study aims to determine the number of infiltration wells needed to reduce the risk of flooding in Sunyaragi Urban Village, Cirebon City. The research employs descriptive methods using Arc-GIS remote sensing and quantitative methods, including hydrological analysis to measure rainfall intensity, hydraulics analysis to assess drainage channel capacity, and infiltration well analysis to determine the required number of infiltration wells. Based on the analysis results, the maximum runoff discharge value in the 5-year return period on St. Taman Pemuda is 0.00562 m³/sec, indicating that eight infiltration wells are needed. These wells are planned to be cylindrical, with a diameter of 1 m and a depth of 3 m, achieving an efficiency value of 85.04% in reducing runoff discharge.